Supervision of the execution of orders to conduct covert investigative (detec-tive) actions during the investigation of looting and robbery - Грібов, М.Л. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2015)
The relevance of researching the supervision of the execution of orders to conduct covert investigative (detective) actions during the investigation of looting and robbery is highlighted. A list of covert investigative (search) actions that can be carried out to investigate looting and robbery is provided. The role of the prosecutor in covert investigations of looting and robberies is outlined. The object and means of prosecutorial control over covert investigative (search) actions during the investigation of looting and robberies are defined. The subject of supervision over the activities of units executing orders to conduct covert investigative (search) actions in investigating looting and robbery includes: the presence of formal grounds provided by law for such actions; compliance with legal orders and content restrictions regarding these activities in terms of time, space, and facilities, as well as the scope and application of means. The means of supervision over the activities of units executing orders to conduct covert investigative (detective) actions involve studying the documents required for a comprehensive examination of the subject (rulings of the investigating judge, orders, reports of covert investigative (detective) actions, and their annexes). Keywords: procurator; covert investigative (detective) action; operational units, looting, robbery

Розкрито особливості прокурорського нагляду за роботою оперативних підрозділів з виконання доручень на проведення негласних слідчих (розшукових) дій при розслідувані грабежів та розбоїв. Визначено його предмет та засоби. Ключові слова: прокурорський нагляд, негласні слідчі (розшукові) дії, оперативні підрозділи, грабіж, розбій.
Прокурорський нагляд за виконанням доручень на проведення негласних слідчих (розшукових) дій при розслідувані грабежів та розбоїв